Inputs to the local shelter plan of the municipality of Batad, Iloilo - Ruego, Ma. Regie (University of the Philippines Visayas, 2015)
Housing is one of the basic social needs that influences the qualty of life and welfare of the country's population. Providing poor families with secure tenure is one of the Millennium Development Goal targets which the government, the private sector and civil society groups must address responsively. This is however challenging in the Philippines where housingcondition is characterized by a sheer demand for affordable housing units and the proliferation of informal settlers in danger areas, government-owned and private lands and government infrastructure sites. Compounding these challenges is the increased frequencyand intensity of natural disasters and climate change to which poor families in coastal areas are most vulnerable. In this context that, local government units collaborate with the national government and civil society organizations to formulate a shelter plan that is disasterresponsive and in sync with the prevailing socio-economic conditions of target income groups. Guided by the national laws governing the preparation of a local shelter plan and a conceptual framework that employs low-cost housing technology, environmental safety and resiliencyThe group employed focus group discussions with 17 LGU and sectoral representatives, key informant interviews, stakeholders analysis and secondary data revierw to assess the current and future housing and upgrading needs and their implications to land use and availableresources of the Municipality. Thematic coding was used to analyze FGD responses and key informant interview results. A variety of tools for social development and land use planning were also adopted in the computation of new housing units and analysis of housing affordability and land requirements. This report shows that at the time of data collection, there were a relatively large number of informal settler in Batad found mostly in private-owned lands and danger zones.. Majority of them resided in substandard structures and basic services such as water, sanitation, road access and drainage were either lacking or inadequately maintained. Two major housing design option for the lowest-income household groups were single detached and duplex using the Interlocking Compresses Earth Block ICEB) Technology. The group proposed only two financing schemes for the two lowest income brackets that encouraged the participation of different stakeholder either in land acquisition, land development and housing construction. Within the scope of planning workshop output,some important reflections were drawn to improve the quality of data and the overall process. Among the proposed recommendations were to increase awareness of the LGU officials about their housing options and financing schemes, encourage participation of private service providers and potential NGO partners in the shelter planning process and improve the municipality's data banking system to serve as benchmark in plan formulation.